2007
DOI: 10.1111/j.1365-2052.2007.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations within the FGF5 gene are associated with hair length in cats

Abstract: Hereditary hair length variability in mice and dogs is caused by mutations within the fibroblast growth factor 5 (FGF5) gene. The aim of this study was to evaluate the feline FGF5 orthologue as a functional candidate gene for the long hair phenotype in cats, which is recessive to short hair. We amplified the feline FGF5 cDNA and characterised two alternatively spliced transcripts by RT-PCR. Comparative cDNA and genomic DNA sequencing of long- and short-haired cats revealed four non-synonymous polymorphisms in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 10 publications
1
75
0
2
Order By: Relevance
“…Recent studies have indicated that all long-hair-associated mutations follow a recessive mode of inheritance, and allelic heterogeneity of FGF5 mutations causes the long-hair phenotype in dogs (Dierks et al, 2013). Similarly, mutations within the FGF5 gene are associated with hair length in cats (Drögemüller et al, 2007;Kehler et al, 2007). Using a combination of whole-exome sequencing and homozygosity mapping, Higgins et al (2014) identified distinct pathogenic mutations within the human FGF5 gene in several additional trichomegaly families.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated that all long-hair-associated mutations follow a recessive mode of inheritance, and allelic heterogeneity of FGF5 mutations causes the long-hair phenotype in dogs (Dierks et al, 2013). Similarly, mutations within the FGF5 gene are associated with hair length in cats (Drögemüller et al, 2007;Kehler et al, 2007). Using a combination of whole-exome sequencing and homozygosity mapping, Higgins et al (2014) identified distinct pathogenic mutations within the human FGF5 gene in several additional trichomegaly families.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the angora mouse mutant carries a 2-kb loss-of-function deletion in Fgf5 and displays a delayed catagen onset and excessively long truncal hair [7]. Loss-of-function mutations associated with long-hair phenotypes have been described in several mammalian species including mice [4,8], dogs [9,10] and cats [11,12], which support a conserved role of FGF5 in the regulation of hair growth.…”
Section: Introductionmentioning
confidence: 99%
“…The best defined regulator of anagen length is FGF-5. Mutation of Fgf-5 leads to a prolonged anagen phase in many species (Hebert et al 1994;Drogemuller et al 2007;Cadieu et al 2009). In the mouse, Fgf-5 is expressed in outer root sheath cells at the base of the follicle in late anagen, some of which abut the DP (Hebert et al 1994).…”
Section: Termination Of Anagenmentioning
confidence: 99%